2019
DOI: 10.24198/jaab.v2i2.22641
|View full text |Cite
|
Sign up to set email alerts
|

Fraudulence Financial Statements Analysis using Pentagon Fraud Approach

Abstract: This study aims to examine the influence of variables, namely pressure, opportunity, rationalization, competence, and arrogance on fraudulent financial statements of companies listed in Indonesia Stock Exchange. The subject of the study is the food and beverage manufacturing firms. The period of investigation is the year 2015 – 2017. This study used purposive sampling technique.  In total, there are 36 foods and beverage manufacturing firms involved in this study. The data was generated from the firm’s annual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 2 publications
3
5
0
6
Order By: Relevance
“…Semakin sering terjadi pergantian dewan direksi akan berpengaruh signifikan terhadap fraudulent financial reporting (Triyanto, 2019). Pergantian dewan direksi dilakukan untuk meningkatkan kinerja perusahaan pada periode sebelumnya.…”
Section: Pergantian Dewan Direksiunclassified
“…Semakin sering terjadi pergantian dewan direksi akan berpengaruh signifikan terhadap fraudulent financial reporting (Triyanto, 2019). Pergantian dewan direksi dilakukan untuk meningkatkan kinerja perusahaan pada periode sebelumnya.…”
Section: Pergantian Dewan Direksiunclassified
“…Prediction of positive influence refers to the results of Saputra & Kesumanignrum (2015) and Triyanto (2019), which states that the Change of directors has a positive and significant effect. Change of directors is one of the company's efforts to eliminate directors who are considered aware of fraud by the company, and changes in directors are considered to reduce the effectiveness of company performance due to cultural changes implemented by new directors that require a long time to adapt.…”
Section: H6: Change In Auditor Partially Has a Positive Effect On Fraudulent Financial Reportingmentioning
confidence: 99%
“…The arrogance of a CEO can be known through the number of CEO photos posted on the financial statements because a CEO will tend to display or show off the position he has (Triyanto, 2019). The results showed that partially the frequent number of CEO's pictures (CEOPIC) did not affect fraudulent financial reporting.…”
Section: Effects Of Arrogance Proxied By Frequent Number Of Ceo's Picture On Fraudulent Financial Reportingmentioning
confidence: 99%
“…Peneliti selanjutnya dapat mengambil konsep dari Fraud Pentagon ketika teori tersebut merupakan teori terbaru dalam mendeteksi motivasi untuk melakukan fraud. Penelitian ini selanjutnya dapat mengambil referensi dari jurnal dengan judul Fraudulence Financial Statements Analysis using Pentagon Fraud Approach oleh Triyanto (2019). (3) Adapun mahasiswa yang…”
Section: Simpulanunclassified